PENENTUAN POTENSI EKSTRAK KULIT BATANG TUMBUHAN SIKKAM (Bischofia javanica Blume) SEBAGAI ANTIOKSIDAN DENGAN METODE DPPH DAN SITOTOKSIK DENGAN METODE BSLT - Dapot Parulian Manurung; Agus Sundaryono; Hermansyah Amir (University of Bengkulu, 2020)
This study aims to determine the level of antioxidant activity of Sikkam bark extract (Bischofia javanica Blume) and its potential as an anticancer agent. This research was conducted in November 2018 - April 2019 in the Laboratory of Chemical Education Guidance and Counseling and Basic Science Laboratory, University of Bengkulu. The sample in this study was obtained from Gunung Mariah village in Simalungun district, North Sumatra. The method used in this study was extraction using maceration, liquid-liquid fractionation, phytochemical test, DPPH (Diphenylpicrylhiydrazyl) test and BSLT test (Brine Shrimp Lethality Test). Extraction maceration using ethanol 96%, fractionation using a solvent n-hexane and ethyl acetate, phytochemical tests using Mayer's reagent, Lieberman-Burchard, FeCl3 1% and H2SO4 2N, antioxidant test using DPPH (1,1-diphenyl-2-picrylhydrazyl) and cytotoxic tests using shrimp Artemia salina Leach larvae. The results of the study on maceration of 800 grams of Sikkam bark obtained a crude extract of 53.6 grams (6.7%). Fractionation from 10 grams of crude extract obtained 7.24 gram ethanol fraction (72.4%), ethyl acetate fraction 2.14 gram (21.4%) and n-Hexane fraction 0.39 gram (3.9%). Phytochemical test results obtained the content of alkaloids, flavonoids, tannins, saponins and terpenoids with the highest yield on tannin compounds. The antioxidant activity test results obtained IC50 values in crude extracts of 20.94 ppm, ethanol fraction 36.29 ppm, ethyl acetate fraction 83.28 ppm and n-Hexane fraction 39.13 ppm which showed that crude extract, ethanol fraction, n-Hexane fraction were categorized as very strong antioxidants and Ethyl acetate fraction is categorized as a strong antioxidant. The cytotoxic test results using crude extract obtained an LC50 value of 54,827 ppm which showed that Sikkam bark extract was toxic so that it was potential as an anticancer agent.